Psychosocial mechanisms of a behavioral treatment for urinary incontinence of prostate cancer survivors. Issue 2 (3rd March 2020) - Zhang, Amy Y.; Burant, Christopher; Fu, Alex Z.; Strauss, Gerald; Bodner, Donald R.; Ponsky, Lee
Abstract: Purpose : We examined underlying psychosocial processes of a behavioral treatment for urinary incontinence (UI) of prostate cancer survivors. Design : Secondary analysis of data collected from a clinical trial. Sample : Two hundred forty-four prostate cancer survivors who participated in a clinical trial of behavioral intervention to UI as intervention or control subjects. Methods: The participants had a 3-month behavioral intervention or usual care and were followed up for an additional 3 months. They were assessed at baseline, 3, and 6 months. Latent growth curve models were performed to examine trajectories of each study variable and relationships among the variables. Findings : Increasing self-efficacy and social support were significantly and independently associated with more reduction of urinary leakage frequency over time. Implications for psychosocial oncology : Providing problem-solving skills and social support, including peer support, are essential for empowering patients to reduce UI.